Neutrinoless double beta decay in the economical 3-3-1 model - Soa, Dang Van; Thao, Nguyen Huy; Dong, Phung Van; Huong, Trinh Thi; Long, Hoang Ngoc (Communications in Physics, 2008)
Possible contributions to neutrinoless double beta (ββ)0ν decay in the economical 3-3-1 modelare discussed. We show that the (ββ)0ν decay in this model is due to both sources—MajoranaL and Dirac D neutrino masses. If the mixing angle between charged gauge bosons, thestandard model W and bilepton Y , is in range of the ratio of neutrino masses L/D, boththe Majorana and Dirac masses simultaneously give contributions dominant to the decay. As results,constraints on the bilepton mass are also given.